A chemical study of the essential oil of Pinus kesiya Royle ex Gordon (Fam. Pinaceae) - Javier, Nora U. Remo 1945-
A colorless essential oil which turned yellowish after keeping for some time was obtained from the fresh leaves of Pinus kesiya Royle ex Gordon formerly known as Pinus insularis Endl. (Fam. Pinaneae). Oil yield was 0.48% and moisture content was 54.67%. The physicochemical properties of the oil are the following: specific gravity (d25/25)= 0.8913; refractive index (n20/D) = 1.4785; oprical rotation (o26/D) = 23.960; acidic value = 4.52, ester value = 7.43; ester value after acetylation = 19.39; saponification value = 12.55. TLC and gas chromatography of the oil indicated the presence of o-pinene, d-limonene and bornyl acetate. IR analysis and GC of the oil indicated the predominance of o-pinene.